#TITLE_ALTERNATIVE# - RESA ADAM GUNAWAN, R.
In this research, the author perform sensitivity test to TurboEdit algorithm, forward and backward moving window averaging (FBMWA), and second-order time difference phase ionospheric residual (STPIR) using three different conditions of data acquisition, during normal condition, geomagnetic storm condition, and the peak of solar cycle 24. Combination of FBMWA and STPIR can uniquely determine the cycle slips in each frequency, and then they are used to repair the cycle slips. The results show that when the noise is high, TurboEdit algorithm fails to detect small cycle slips. Also, in this sensitivity test, FBMWA-STPIR can succesfully detect all the cycle slips. However, after performing re-detection to the repaired data, there are some unrepaired cycle slips especially when the peak of solar cycle 24 data